Pemberdayaan Masyarakat Dalam Produksi Pupuk Organik Untuk Mendukung Pertanian Berkelanjutan - Jeka Widiatmanta; Agung Setya Wibowo; Zunita Wulansari; Mukh Taofik Chulkamdi (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to empower the community in organic fertilizer production as a step to support sustainable agricultural practices. The overuse of chemical fertilizers has been shown to damage soil structure and reduce long-term productivity. Therefore, there needs to be a systematic effort to reduce dependence on chemical fertilizers and increase the use of organic fertilizers (FMIPA UI 2020). Through this program, the community is provided with training and assistance in the production process of organic fertilizer from easily accessible natural materials, such as crop residues, animal manure, and household waste. The methods used include lectures, demonstrations, and hands-on practice in the field, so that participants are able to apply the knowledge independently. The results of this program show an increase in the community's understanding and skills in producing organic fertilizer, as well as a commitment to implementing sustainable agriculture on their farms. With the increased use of organic fertilizer, it is expected that soil quality can be improved and agricultural productivity can be maintained sustainably. This activity is a concrete step in supporting environmentally friendly agriculture and improving the economic welfare of the community through reduced fertilizer costs.